2016
DOI: 10.5812/archcid.37205
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii Infection in Patients with Alzheimer’s Disease

Abstract: Background: Toxoplasmosis is one of the most important diseases in humans and animals. Almost one-third of the human population around the world is infected with toxoplasmosis. The agent of this parasitic disease is a protozoan called Toxoplasma gondii (T. gondii) that causes encephalitis in people with suppressed immune systems and abortion, mental retardation and chorioretinitis in the fetus. Alzheimer's disease (AD) is the most important neurodegenerative disease. Objectives: Due to the high prevalence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…There are numerous studies on the role of T. gondii in neurological diseases. Menati Rashno et al reported that the overall prevalence of T. gondii infection was 66% and 56.3% in patients with AD and controls, respectively (19). In agreement with the present study, the toxoplasmosis prevalence was higher in the test group than in the healthy group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are numerous studies on the role of T. gondii in neurological diseases. Menati Rashno et al reported that the overall prevalence of T. gondii infection was 66% and 56.3% in patients with AD and controls, respectively (19). In agreement with the present study, the toxoplasmosis prevalence was higher in the test group than in the healthy group.…”
Section: Discussionsupporting
confidence: 92%
“…This finding suggested that consuming meat in any form (cooked or raw) can increase the risk of toxoplasmosis and this is especially important in high-risk groups. Menati Rashno et al found similar results that the protein content was higher in the diet of people who had positive IgG titers against toxoplasmosis than in the diet of people who were using more vegetables (19).…”
Section: Discussionmentioning
confidence: 79%
“…Prandota suggests that Alzheimer's may be associated with congenital transmission; however, there was no significant correlation between them [ 71 ]. More recent studies with larger populations did not detect correlations or statistical significance between Alzheimer's and T. gondii infection [ 72 78 ]. Thus, it is undetermined if Alzheimer's disease and T. gondii infection are linked.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…For a long time, toxoplasmosis has been known as an opportunistic infection in the immunocompromised patients. It is also known as the third leading cause of death in AIDS patients after Pneumocystis and Cryptosporidium , which makes it an important issue (12–14). In this study, 55.31% of patients with thalassemia major and 37.02% of healthy individuals were positive for anti- Toxoplasma antibodies.…”
Section: Discussionmentioning
confidence: 99%